Contemporary Kidney Transplantation (Organ and Tissue Transplantation,, 2018)
This book provides a comprehensive guide to successful kidney transplantation in the highly regulated environment of today. It covers the history of kidney transplant to highlight innovations that have made kidney transplantation so successful as well as the new deceased donor kidney allocation strategy and postulates what types of changes might occur with this new policy. The book highlights special areas of nephrology concern in kidney transplantation, especially diseases likely to recur following transplant. It deals with many of the medications used in kidney transplantation including different commonly used antirejection protocols. It also provides a complete reference on the various operations involved in kidney transplantation. The text includes detailed pictures and surgical technique sections on cadaveric kidney transplantation and living kidney transplantation. It includes information on living kidney donation surgery with a chapter dedicated to the minimally invasive techniques that have been popularized in the last fifteen years. Some coverage on open living kidney donation is presented. Included in this section is discussions of how to handle certain operative challenges like severe atherosclerosis, venous sclerosis and various urinary system aberrancies. Comprehensive coverage of common surgical complications is presented including management of urinary strictures, urinary leaks, lymphoceles, vascular problems following transplant, and what steps shoul d be taken when an early kidney transplant biopsy is necessary. It also covers in detail what is required for maintenance of health after kidney transplantation including the major risks for graft loss as well as what disease processes kidney transplant patients are particularly vulnerable to.